Dyspnea in Children as a Symptom of Acute Respiratory Tract Infections and Antibiotic Prescribing - Risteska-Nejashmikj, Valentina; Stojkovska, Snezhana; Stavrikj, Katarina (Scientific Foundation SPIROSKI, 2018)
Dyspnea is an unpleasant feeling of breathing difficulty, shortness of breath and inability to satisfy the hunger for air. The role of family physicians is to be prepared to recognise dyspnea as a symptom of acute respiratory infections (ARI), to perform triage and managing of children with acute dyspnea and make continuous education of parents. In the treatment of acute dyspnea more important is to treat dyspnea as a symptom than the prescribing of antibiotics (AB). Nowadays, even more often large amount of children, because of the noncompliance in the treatment and the pressure from the parents, unnecessary is hospitalised and frequently used antibiotics: According to the guidelines, a small percentage of children with ARI should be treated with AB. The rate of antibiotic prescription should be around 15-20% and lower.